Transição de regimes cambiais no Brasil pós julho de 1994: uma análise de Vetores Auto-Regressivos (VAR) e causalidade - Cardoso, Carlos de Almeida (2004)
The present dissertation analyses the transition of exchange rates regimes in Brazil (1994- 2003). Its main hypothesis is that there were important changes in the interaction of the following variables: exchange, interest and inflation rates as well as domestic currency. Besides that, this work examines the relevance of fear of floating for the Brazilian case. Our results show significant changes in the dynamics occurred among the variables listed previously due to the transition from a rigid exchange rate to a more flexible one and this is, in a way, a confirmation of our initial hypothesis. As for the fear of floating problem, our findings are distinct when it comes to analyzing the Brazilian experience. The reason for such distinction is that what was found for the Brazilian data is not similar to tests performed with data from other countries which went through some type of exchange rate transition, which means that the credibility problem seems not to be so crucial. On the other hand, what was found in our tests for Brazil is quite close to some other important experiences especially when one realizes that, in the context of macroeconomic policy, the exchange rate is a relevant variable and that it has got an important connection to the behavior of prices (inflation) and also other economic policy instruments (interest rate, for instance). Moreover, it is important to point out the need to adopt an active macroeconomic policy regarding the exchange rate, that is, there may be times when the policymaker may feel, to some extent, the need to impose some type of control to the exchange rate.